The historical Coffin–Lowry syndrome family revisited: Identification of two novel mutations of RPS6KA3 in three male patients2. Issue 9 (7th July 2014) - Nishimoto, Hiromi Koso; Ha, Kyungsoo; Jones, Julie R.; Dwivedi, Alka; Cho, Hyun‐Min; Layman, Lawrence C.; Kim, Hyung‐Goo
<x xml:space="preserve">Abstract</x> Coffin–Lowry syndrome (CLS) is a rare X‐linked dominant disorder characterized by intellectual disability, craniofacial abnormalities, short stature, tapering fingers, hypotonia, and skeletal malformations. CLS is caused by mutations in the Ribosomal Protein S6 Kinase, 90 kDa, Polypeptide 3 (RPS6KA3) gene located at Xp22.12, which encodes Ribosomal S6 Kinase 2 (RSK2). Here we analyzed RPS6KA3 in three unrelated CLS patients including one from the historical Coffin–Lowry syndrome family and found two novel mutations. To date, over 140 mutations in RPS6KA3 have been reported. However, the etiology of the very first familial case, which was described in 1971 by Lowry with detailed phenotype and coined the term CLS, has remained unknown. More than 40 years after the report, we succeeded in identifying deposited fibroblast cells from one patient of this historic family and found a novel heterozygous 216 bp in‐frame deletion, encompassing exons 15 and 16 of RPS6KA3. Drop episodes in CLS patients were reported to be associated with truncating mutations deleting the C‐terminal kinase domain (KD), and only one missense mutation and one single basepair duplication involving the C‐terminal KD of RSK2 in the patients with drop episode have been reported thus far. Here we report the first in‐frame deletion in C‐terminal KD of RPS6KA3 in a CLS patient with drop episodes. © 2014 Wiley Periodicals, Inc.